From Grids to Service and Pervasive Computing - Priol, Thierry (Springer, 2017)
Grids are a crucial enabling technology for scientific and industrial development. Peer-to-peer computing, grid, distributed storage technologies, emerging web service technologies, and other types of networked distributed computing have provided new paradigms exploiting distributed resources. Grids are revolutionizing computing as profoundly as e-mail and the Web.